2015
DOI: 10.1007/s00280-015-2875-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for pegylated liposomal doxorubicin-induced palmar-plantar erythrodysesthesia over time: assessment of monocyte count and baseline clinical parameters

Abstract: Contrary to most acute toxicities, PPE occurred more frequently after several cycles, suggesting a PLD body accumulation through repeated cycles. PPE was more frequent in pts older than 70 years. Monocyte subpopulations may have different roles on PLD metabolism and warrant further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Inter‐individual variability in monocyte subpopulations was observed, representing three distinct populations with different immunological responses: classical (CD14++ CD16‐‐), non‐classical (CD14+ CD16++), and intermediate (CD14++ CD16+). While a majority displayed similar characteristics to healthy populations, two patients had lower populations of nonclassical monocytes (3.5 and 4.5 versus 10.9%) . Two others showed a decreased proportion of classical monocytes and a higher level of nonclassical and intermediate monocytes.…”
Section: The Mps In Clinical and Preclinical Modelsmentioning
confidence: 84%
See 3 more Smart Citations
“…Inter‐individual variability in monocyte subpopulations was observed, representing three distinct populations with different immunological responses: classical (CD14++ CD16‐‐), non‐classical (CD14+ CD16++), and intermediate (CD14++ CD16+). While a majority displayed similar characteristics to healthy populations, two patients had lower populations of nonclassical monocytes (3.5 and 4.5 versus 10.9%) . Two others showed a decreased proportion of classical monocytes and a higher level of nonclassical and intermediate monocytes.…”
Section: The Mps In Clinical and Preclinical Modelsmentioning
confidence: 84%
“…This study demonstrated the association between a reduction in pre‐cycle monocyte count and decreased PLD clearance from cycles 1 to 3 of therapy ( p = 0.09) . A recent pilot study further assessed the monocyte subpopulations before PLD administration in a small patient population ( n = 9) . Inter‐individual variability in monocyte subpopulations was observed, representing three distinct populations with different immunological responses: classical (CD14++ CD16‐‐), non‐classical (CD14+ CD16++), and intermediate (CD14++ CD16+).…”
Section: The Mps In Clinical and Preclinical Modelsmentioning
confidence: 84%
See 2 more Smart Citations
“…They also reported that PLD clearance is correlated with age, and a longer PLD half-life is correlated with the development of HFS [ 19 ]. Another retrospective study of 88 patients found that HFS is more common with subsequent cycles of PLD and older age [ 20 ].…”
Section: Introductionmentioning
confidence: 99%